Microalgal diversity enhances water purification efficiency in experimental microcosms - Zhou, Songlin; Li, Wei; He, Shuqiang (Frontiers in Ecology and Evolution, 2023)
The losses of biodiversity have impaired functioning and provision of ecosystem services, and the relationship between biodiversity and ecosystem functioning has emerged as a central issue in environmental sciences. However, the majority of relevant studies are conducted in terrestrial ecosystems, and they focus predominantly on the relationship between community diversity and biomass production of terrestrial vegetation. At present, water eutrophication represents an increasingly serious problem worldwide, and the use of aquatic organisms for improving water quality represents a promising approach. However, more focus is placed on the selection of certain aquatic organisms with good performance, but neglects the effects of biodiversity in the process of water purification and the underlying mechanisms. In the present study, five microalgal species commonly found in freshwater ecosystems were used to assembly experimental microcosms with varying microalgal richness and composition. We analyzed the relationship between microalgal diversity and nitrogen removal efficiency based on mixed-effect models, and further explored the underlying mechanism of microalgal diversity in the process of water quality improvement. The results showed that with an increase in microalgal diversity, nitrogen removal efficiency of microalgal communities also increased. A further analysis of the impacts of microalgal diversity showed that the complemenatriy effect increased while the selection effect decreased with an increase in microalgal diversity. Meanwhile, there was a significantly positive relationship between microalgal diversity and the total abundance of microalgae. On the one hand, the present study clearly demonstrates two positive diversity-ecosystem functioning relationships. On the other hand, the present study also reveals the underlying mechanism by which microalgal diversity influences nitrogen removal efficiency, namely, high-diversity microalgal communities could use limiting nutrients such as nitrogen in a more efficient and complementary manner (e.g., stronger complementarity effect in high-diversity communities), convert them into higher aggregate community properties (e.g., higher total abundance of microalge in high-diversity communities), and thus exhibit higher purification capacity (e.g., higher nitrogen removal efficiency in high-diversity communities). Under the scenario that global ecosystems are experiencing high rates of anthropogenic nutrient inputs, the use of diverse microalgal species with proper management may help provide a promising approach for improving water quality.